A descriptive assessment of a broad range of food-related parenting practices in a diverse cohort of parents of preschoolers using the novel Real-Time Parent Feeding Practices Survey - K. A. Loth; Z. Ji; J. Wolfson; D. Neumark-Sztainer; J. M. Berge; J. O. Fisher (BMC, 2022)
Abstract Background Much of the research to-date on food parenting has evaluated typical use of various parent feeding practices via questionnaire. The Real-Time Parent Feeding Practices Measurement survey was developed for use within an Ecological Momentary Assessment (EMA) protocol to capture momentary use of parent feeding practices in real-time. Methods This manuscript describes the development of the EMA-based Real-Time Parent Feeding Practices survey and highlights initial descriptive data on the real-time use of 22 individual parent feeding practices (e.g., pressure-to-eat, guided choices, etc.) as reported via EMA by parents of preschool-aged children (n = 116) over a 10-day data collection time period. A total of 3382 eating occasions were reported, with an average of 29.2 reported eating occasions per participant. Results Results revealed that most participants used a variety of food-related parenting practices day-to-day that span four higher-order domains: structure, autonomy support, coercive control and indulgence. Supportive feeding practices, defined as those from the structure and autonomy support domains, were reported most frequently, with one or more structure behavior (e.g., specific mealtime rules/routines) was used at 88.9% of reported eating occasions and one or more autonomy support behavior (e.g., involvement of the child in meal preparation) was used at 87.3% of eating occasions. While unsupportive feeding practices, defined as practices from within the coercive control (e.g., pressure-to-eat) and indulgent (e.g., anticipatory catering) feeding domains, were reported less frequently, one or more behaviors from each of these domains were still reported at over 25% of all eating occasions. Conclusions Results of the current study take a next step towards deepening our understanding of the use of a broad range of food-related parenting practices in real-time. Findings revealed that the vast majority of practices used by parents fall within the structure and autonomy support domains. However, most parents did not exclusively use supportive or unsupportive practices, rather they used a combination of food-related parenting practices across all domains. Future research should continue to explore a broad range of food-related parenting practices and seek to understand how parent approaches to feeding are associated with long-term child outcomes, including dietary intake, food preferences, and eating patterns.